Relatività per principianti Fondamenti di Relatività Speciale e Generale con un breve Compendio di Fisica Classica - Borghero, Francesco (UNICApress, 2021)
This book is designed to explain, in the simplest way possible, the Theories of Special and General Relativity to students who are approaching them for the first time. The contents of these two theories are now part of the cultural background needed by every physicist and mathematician, and, in particular, they constitute an indispensable body of knowledge for anyone involved in physics, astrophysics and cosmology.